INFLUENCE OF COLLABORATIVE STRATEGIC READING (CSR) IN TEACHING READING COMPREHENSION - Saori, Sopian (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2015)
This study is aimed to find out whether there is a significant difference in reading achievement between the students who are taught by using CSR and that of the students who are taught by using another technique. This study used quasi experimental design. This research was conducted from January 13 to February 17, 2014. The participants of this study were the second year students of State Islamic Junior High School of Yogyakarta II. There were two intact classes taken as the subject of this study. Each class consisted of 32 students performing as experimental group and 32 students as a control group. The pretest and posttest were used as the instrument to collect the data. Descriptive and inferential statistics were used to analyze the data. The research findings showed that after students were taught by using collaborative strategic reading, the students? mean score of the experimental group was higher (68.12) than that of the mean score of the control group (60.75) with mean difference 7.22. The F value (12.74) was higher than the F table (4.00) with 5 % level in the degree of freedom was 60 and the p value (.001) was lower than (.05).